Self-paced intermittent-sprint performance and pacing strategies following respective pre-cooling and heating - Skein, M.; Duffield, R.; Cannon, J.; Marino, F. E. (European Journal of Applied Physiology, 2012)
This study examined the effects of pre-exercise cooling and heating on neuromuscular function, pacing and intermittent-sprint performance in the heat. Ten male, team sport athletes completed three randomized, counterbalanced conditions including a thermo-neutral environment (CONT), whole body submersion in an ice bath (ICE) and passive heating in a hot environment (HEAT) before 50 min of intermittent-sprint exercise (ISE) in the heat (31 + 1°C). Exercise involved repeated 15 m maximal sprints and self-paced exercise of varying intensities. Performance was measured by sprint times and distance covered during self-paced exercise. Maximal isometric contractions were performed to determine the maximal voluntary torque (MVT), activation (VA) and contractile properties. Physiological measures included heart rate (HR), core (T core) and skin (T skin) temperatures, capillary blood and perceptual ratings. Mean sprint times were slower during ICE compared to HEAT (P < 0.05). Total distance covered was not different between conditions, but less distance was covered during HEAT in 31-40 min compared to CONT, and 41-50 min compared to ICE (P < 0.05). MVT was reduced post-exercise compared to post-intervention in CONT and HEAT. VA was reduced post-intervention in HEAT compared to CONT and ICE, and post-exercise compared to ICE (P < 0.05). HR, T core and T skin during exercise were lower in ICE compared to CONT and HEAT (P < 0.05). Sprint times and distance covered were not affected by ICE and HEAT conditions compared to CONT. However, initial sprint performance was slowed by pre-cooling, with improvements following passive heating possibly due to altered contractile properties. Conversely, pre-cooling improved exercise intensities, whilst HEAT resulted in greater declines in muscle recruitment and ensuing distance covered.